Determinant Factors Influencing the Performance of Health Workers at Karang Rejo Primary Health Center, Tarakan City - Sri Wahyu Ekowati; Byba Melda Suhita; Prima Dewi Kusumawati (Utan Kayu Publishing, 2026)
Run optimally. The calculation of the need for health workers is usually based on several things, such as the type of disease that is widely encountered in the community, the number and burden of services that must be handled, the availability of health facilities, and certain ratios or standards that have been set. The purpose of this study is to analyze the influence of reinforcement, competence and workload on the performance of health workers at the Karang Rejo Health Center, Tarakan City. The design of this study is an observational quantitative research with a cross sectional approach. The total population was 146 respondents while the sample of 107 respondents was taken using the Simple Random Sampling technique. Based on the results of the Ordinal Regression analysis, it is known that the variables of reinforcement, competence, and workload partially have a significant influence on the performance of health workers at the Karang Rejo Health Center, Tarakan City, which is shown by the p-value of 0.016 for reinforcement, 0.007 for competence, and 0.016 for workload (p < 0.05), so that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. These findings show that the better the implementation of reinforcement provided by the leadership, the higher the level of competence that health workers have, and the more appropriate the workload management, the performance of health workers tends to increase. Thus, the performance of health workers is not only influenced by individual factors such as competence, but also by organizational factors in the form of reinforcement and workload, which together play an important role in supporting the improvement of the quality of health services at the Karang Rejo Health Center, Tarakan City.